The effects of recreational cardio fitness programs on the body composition of young women - Mensur Vrcić; Ratko Pavlović; Erol Kovačević; Sid Solaković; Silma Hadžimuratović (IP Iermakov S.S., 2023)
Background and study aim. Group fitness programs are a form of programmed physical exercises with the aim of improving health, aesthetic appearance, satisfying the motivation to preserve health and reduce body weight. The aim of this study was to determine the effects of an experimental cardio fitness program on the morphological status of female subjects aged 21.5 ± 3.5 years. Material and methods. The experimental program was implemented over a period of three months (12 weeks), with a weekly frequency (3 x 20-60 min). Initial and final measurements were performed and Body weight, Body fat percentage, Body fat mass, Free fat mass, Body muscle mass, Body mass index and Basal metabolism rate were analyzed. All test subjects have their doctor's confirmation that they are healthy and can undergo training loads in a planned and clearly defined cardio program. Results. The exercise program on cardio equipment caused changes in all body composition parameters between the initial and final measurements t-test (except for muscle mass). The total average Body weight at the initial-final measurement (66.45 vs. 64.70kg; t= 5.225, p<0.000), which represents a difference of -1.75kg after the program. Conclusions. The assumption is that a controlled and monitored program with a special focus on nutrition would lead to even more precise results on the effects on body composition. Continuous application of the content of this program throughout the entire one-year macrocycle with a higher weekly frequency would certainly give even more significant results.